Alat angkut tradisional daerah Sumatera Selatan - Yanuar T.M.; Dahlan, M.; Azharizal; Departemen Pendidikan dan Kebudayaan. Direktorat Jenderal Kebudayaan. Museum Sumatera Selatan ([Palembang] : Departemen Pendidikan dan Kebudayaan, Direktorat Jenderal Kebudayaan, Museum Sumatera Selatan, 1987)
Traditional transportation, Sumatera Selatan Province.
Keywords: Transportation -- Indonesia; Sumatera Barat (Indonesia) -- Social life and customs